Green synthesis and characterization of silver nanoparticles (agnps) using artemisia annua l. and its Anti-bacterial, anti-fungal activity - RENUGA DEVI KARTHIKEYAN,; JULIUS AMALDAS, (International Journal of Pharma and Bio Sciences, 2018)
In the recent times, biomedical and pharmacological applications of Silver nanoparticles (AgNPs) have gained much attention owing to its array of pharmacological effects like anti-bacterial, anti-fungal and anti-cancer activities. In the present study we have attempted to evaluate and endorse the pharmacological effects of green synthesis of AgNPs using Artemesia annua L plant extract. Characterization of Artemesia annua L AgNPs were performed using UV-vis spectroscopy, Energy dispersive X-ray analysis (EDX), Dynamic light scattering (DLS), X-ray diffraction analysis (XRD), Transmission electron Microscopy (TEM) and Fourier Transform infrared spectroscopy (FTIR). A band at 425nm was observed using UV-vis spectra and TEM denotes that the synthesized AgNPs are about 30-35 nm in size and are spherical in nature. Further, its antibacterial activity was assessed using gram-positive bacteria strains, such as B. subtilis and S. aureus and Gram-negative bacteria, such as P. aeruginosa and E. coli and anti-fungal activity was also demonstrated against fungi such as C. albicans and A. niger The results obtained show that the synthesized AgNPs using Artemesia annua L, exert significant biological functions and hence it can be applied in therapeutic applications like anti-cancer activities. Further, we are also interested to study its mechanistic actions, for which studies are currently in progress.